2019
DOI: 10.1016/j.snb.2019.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic biosensors based on screen-printed Prussian Blue electrodes

Abstract: Highlights We present the production of an electrochromic screen-printable paste based on Prussian Blue. These blue electrodes display excellent spectroelectrochemical reversibility and high catalytic activity towards the reduction of H2O2.  These blue electrodes enable both the electrochemical and optical quantitative determination of hydrogen peroxide.  The reported blue electrodes are highly suitable transducers for the construction of oxidase-based biosensors.  A glucose biosensor is presented to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…These results correspond to those obtained when using other voltammetric sensors for the indirect detection of electroinactive compounds [39,43,44,47,48,50].…”
Section: Electrochemical Responses Of Spces Modified In 10 −3 M Phe-1supporting
confidence: 88%
See 1 more Smart Citation
“…These results correspond to those obtained when using other voltammetric sensors for the indirect detection of electroinactive compounds [39,43,44,47,48,50].…”
Section: Electrochemical Responses Of Spces Modified In 10 −3 M Phe-1supporting
confidence: 88%
“…Cobalt Phthalocyanine, an organic semiconductor ensuring sensor stability and sensitivity is another modifier used in the development of CMEs [44][45][46][47]. Due to its chemical composition, Prussian Blue has very good electrochemical properties, being most frequently used in the manufacture of electrochemical (bio)sensors detecting hydrogen peroxide [48][49][50][51][52][53][54][55][56]. These electroactive materials could be used for the development of novel electrochemical sensors for different analysts of great importance such is Phe.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been widely used for the construction of printed and patterned conjugated polymers for solar cells and light‐emitting diodes . In line with previous reports , we propose the use of carrier conductive metal oxide particles dispersed in a resin binder, with the novelty of incorporating the ECP‐Magenta polymer as the electrochromic coating. We have investigated the use of antimony‐doped tin oxide microparticles (ATO/TiO 2 ) as a conducting light‐coloured material for use in spectroelectrochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study demonstrated the fabrication of electrochromic biosensors based on a screen printed electrode for both colorimetric and amperometric sensing (Aller‐Pellitero et al, 2019) The PB modified screen printed electrode was prepared using a screen printable paste, which was made from a chemically synthesized PB nanocomposite. Indium tin oxide or Sb‐doped SnO 2 (ATO) particles and chemically synthesized Prussian blue obtained from the co‐precipitation of two precursors were mixed with binder to make the screen printable PB paste.…”
Section: Resultsmentioning
confidence: 99%